Superficial Radiation Therapy for the Treatment of Nonmelanoma Skin Cancers - McGregor, Sean (J Clin Aesthet Dermatol, 2015)
Superficial radiation therapy has become more widely available to dermatologists. With the advent of more portable machines, it has become more convenient for dermatology practices to employ in an office-based setting. The goal of this paper is to provide a deeper insight into the role of superficial radiation therapy in dermatology practice and to review the current literature surrounding its use in the treatment of both basal and squamous cell carcinomas.